Audio software development : an audio quality perspective - Ekeroot, Jonas (2008)
Audio Technology as an academic discipline at Luleå University of Technology does not yet have a long research tradition and is therefore in the process of forming and establishing its research areas and methods. In that context, this essay treats audio software development from an audio quality perspective. The aim was to identify relevant questions that must be considered during such software development. Audio aspects of the operating systems Windows, Mac OS X and Linux were included in this essay, and the general development perspective was on audio software written in C++ to be run on general purpose CPUs. A research review, comprising literature from different fields such as Audio Engineering, Computer Science and Software Engineering, was conducted to summarize and integrate an overview of the state of knowledge, and at the same time observe what was still missing in the literature. The result can be viewed as a map of questions that constitute the starting point for future research activities, consisting of further literature studies and experiments with software prototypes. Such software prototypes were not developed during the work with this essay. In summary, questions that must be considered during audio software development from an audio quality perspective deal with the audio software signal path through an audio subsystem, the use of floating point audio sample representation, conversions between floating point and fixed point integer audio sample representation, and if and how to apply dither in the context of floating point audio sample representation. Validerat; 20101217 (root)